A CHARACTERISTIC STUDY ON COMBINED PROPERTIES OF FLYASH AND GGBS BRICKS USING INDUSTRIAL FOUNDRY WASTE & CRUSHER DUST - priyadharshini, s.Cynthia; seljah, M.Persis; Ponmalar, M.; Simon, Reshma; Suja, B. (IJRDO - Journal of Mechanical And Civil Engineering, 2016)
Nowadays implementation and utilization of new building materials and industrial waste is being practiced. Due to immense increasing quantities of waste material from industries can be used for the purpose of economical construction and in concern of reducing waste disposal. In general bricks are made by top fertile agricultural soil but by using fly ash, few percent of top fertile agricultural soil is saved. Use of fly ash in brick making also is beneficial in diverse ways. When compared to conventional clay bricks fly ash bricks are stronger, more durable and yet more economical. Also, the manufacturing process of fly ash bricks results in lesser pollution. About GGBS it is a by-product of manufacturing iron it can be partially replaced by cement which will increase the strength of bricks. Foundry waste consists primarily of steel waste and dust from steel industry. Foundry waste can be used in concrete to improve its strength and other durability factors. In the present study the combined properties of brick by partially replacing ground granulated blast furnace slag(GGBS) and fly ash in terms of cement and industrial waste such as foundry waste and crusher dust also used as a filler material which is passed through 150 microns. Quantity of material taken is in terms of parts. Bricks were casted in lab from the best mix obtained and mechanical properties like compressive strength and water absorption were noted